2011
DOI: 10.1007/s10461-011-9953-7
|View full text |Cite
|
Sign up to set email alerts
|

HIV Prevention and Transmission Myths Among Heterosexually Active Adults in Low-Income Areas of South Florida

Abstract: Misconceptions about HIV transmission and prevention may inhibit individuals' accurate assessment of their level of risk. We used venue-based sampling to conduct a cross-sectional study of heterosexually active adults (N = 1,221) within areas exhibiting high poverty and HIV/AIDS rates in Miami-Dade and Broward counties in 2007. Two logistic regression analyses identified correlates of holding inaccurate beliefs about HIV transmission and prevention. Belief in incorrect HIV prevention methods (27.2%) and modes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Examples of these include HIV transmission through casual contact or that HIV transmission only occurs among gay, bisexual, and other sexual minority men. Although scholarship in this area has been limited, the findings from this study are consistent with the results of previous studies conducted in the United States (Beck et al, 2012; Gleason-Morgan et al, 1991; Hughes & Alford, 2017). These studies identified similar myths and misperceptions, such as incorrect transmission beliefs and an association with not knowing one’s status.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Examples of these include HIV transmission through casual contact or that HIV transmission only occurs among gay, bisexual, and other sexual minority men. Although scholarship in this area has been limited, the findings from this study are consistent with the results of previous studies conducted in the United States (Beck et al, 2012; Gleason-Morgan et al, 1991; Hughes & Alford, 2017). These studies identified similar myths and misperceptions, such as incorrect transmission beliefs and an association with not knowing one’s status.…”
Section: Discussionsupporting
confidence: 91%
“…Each example in the table was stated once unless otherwise indicated by a number within parentheses next to the example. (Beck et al, 2012;Gleason-Morgan et al, 1991;Hughes & Alford, 2017). These studies identified similar myths and misperceptions, such as incorrect transmission beliefs and an association with not knowing one's status.…”
Section: > > Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Nowadays however it is well established that AIDS is not confined to homosexual or bisexual men. In fact, heterosexual contact now plays a significant role in continuing the worldwide AIDS epidemic, and specifically the spread of the disease throughout the United States, including Miami-Dade County and South Florida 3 . In particular, heterosexual contact is the primary mode of HIV/AIDS transmission to women.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of knowledge showed by our participants could be explained by misconceptions and myths about HIV prevention and transmission which are widespread, especially among low-income heterosexuals 22 . In our participants, we found two opposite poles of knowledge regarding HIV infections.…”
Section: Discussionmentioning
confidence: 77%